NORMATIVE TEST FOR ENFORCEMENT OF COLONIAL LAW AND MORAL JUSTICE ARTICLE OF CONTROVERS IN THE NATIONAL KUHP BILL - Waluyadi (Journal Indonesia Law and Policy Review, 2022)
Indonesia is an independent country. In criminal law it is still colonized. At first, the implementation of the colonial Criminal Code (KUHP) was only temporary. The law has legalized the adjustment of the implementation of the colonial Criminal Code in the spirit of an independent and sovereign state. I just don't have the courage to do it. The plan to stipulate the original Indonesian Criminal Code was met with demonstrations. In this paper, the problem that will be revealed is what is the normative measure of the enforcement of the colonial Criminal Code in Indonesia and how is the moral justice of the controversial articles in the National Criminal Code Bill. This paper is sourced from normative research. The data used is secondary data. Data collection was carried out by means of a literature study, The data were analyzed qualitatively and presented in descriptive form. From the results of the research, it is known that the Act has legalized the enactment of the colonial Criminal Code in Indonesia, with exceptions. The articles in the Draft Criminal Code which are considered controversial have already accommodated moral values.